Conservative Management of Gallstone Disease in the Elderly Population: Outcomes and Recurrence. (September 2020) - Mora-Guzmán, I; Di Martino, M; Bonito, AC; Jodra, VV; Hernández, SG; Martin-Perez, E
Background & Aims: The prevalence of gallstone disease increases with age, being early cholecystectomy the most accepted treatment in the vast majority of patients in order to prevent complications and recurrence. The aim of this study is to determine the recurrence rate and its possible predictors after initial non-operative management. Materials and Methods: We reviewed a consecutive series of patients, older than 65 years, admitted for a gallstone-related disease and treated with a non-operative management between January 2010 and December 2013. We analyzed comorbidities, clinical data, diagnosis, management, recurrence, and its treatment. Median follow-up after the discharge was 2 years. Recurrence was analyzed by a Kaplan–Meier survival curve. Possible recurrence's predictors were analyzed. Results: The study included 226 patients. Mean age was 80.4 ± 7.2 years, 127 (56%) were female. The main causes of index hospitalization were acute cholecystitis (58%) and biliary pancreatitis (18.1%). After 2 years of follow-up, the recurrence rate was 39.8%; mean time to recurrence was 255.2 ± 42.1 days, 81% of patients recurred within 1 year. Bile duct disease implied a higher recurrence rate than the gallbladder disease group (52% vs 33%, p < 0.001). Subjects with two or more diagnoses during index admission presented higher recurrence rate (32% vs 49%, p < 0.001). Conclusion: More than a third of elderly patients could present a recurrence within 2 years after initial non-operative management. Early cholecystectomy should be considered at index admission in order to prevent recurrence.